Beta-amyloid accumulation in APP mutant neurons reduces PSD-95 and GluR1 in synapses - Claudia G. Almeida; Davide Tampellini; Reisuke H. Takahashi; Paul Greengard; Michael T. Lin; Eric M. Snyder; Gunnar K. Gouras (Neurobiology of Disease, 2005)
Synaptic dysfunction is increasingly viewed as an early manifestation of Alzheimer's disease (AD), but the cellular mechanism by which β-amyloid (Aβ) may affect synapses remains unclear. Since cultured neurons derived from APP mutant transgenic mice secrete elevated levels of Aβ and parallel the subcellular Aβ accumulation seen in vivo, we asked whether alterations in synapses occur in this setting. We report that cultured Tg2576 APP mutant neurons have selective alterations in pre- and post-synaptic compartments compared to wild-type neurons. Post-synaptic compartments appear fewer in number and smaller, while active pre-synaptic compartments appear fewer in number and enlarged. Among the earliest changes in synaptic composition in APP mutant neurons were reductions in PSD-95, a protein involved in recruiting and anchoring glutamate receptor subunits to the post-synaptic density. In agreement, we observed early reductions in surface expression of glutamate receptor subunit GluR1 in APP mutant neurons. We provide evidence that Aβ is specifically involved in these alterations in synaptic biology, since alterations in PSD-95 and GluR1 are blocked by γ-secretase inhibition, and since exogenous addition of synthetic Aβ to wild-type neurons parallels changes in synaptic PSD-95 and GluR1 observed in APP mutant neurons.